Production of tungsten carbide nanoparticles through Micro-EDM and its characterization. (2019) - Yadav, H.N.S.; Bishwakarma, H.; Kumar, N.; Kumar, S.; Singh, P.K.; Mohanty, S.; Das, A.K.
Abstract: The development of nano technologies have created renewed interest among researchers and scientist about various ingenious applications of these nano technologies. Production of nanoparticles with controlled morphology, size, shape and composition, is crucial step toward nano-technological applications. The present paper is focused on production of tungsten carbide nanoparticles through micro-EDM. In micro-EDM process after discharge high heat is generated, this is responsible for melting and evaporating of material in dielectric medium to form nanoparticles. Change in dielectric show the remarkable effect on the Metal Removal Rate (MRR) and Tool Wear Rate (TWR), size, morphological structure of produced nanoparticle. The generated tungsten carbide nanoparticles were characterized by field emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectroscopy. EDS result shows the sample contains carbon and tungsten which form tungsten carbide.